Effect of formulation parameters on the size of PLGA nanoparticles encapsulating bovine serum albumin: a response surface methodology - Adebileje, Tajudeen; Valizadeh, Alireza; Amani, Amir (Journal of Contemporary Medical Sciences, 2017)
Objective Poly (lactic-co-glycolic) acid (PLGA) as a polymeric carrier for medicines has been extensively investigated because of its unique biodegradability and biocompatibility features. In this study, bovine serum Albumin (BSA), a protein which plays a key role in maintaining oncotic pressure was employed as a model protein to be encapsulated into PLGA nanoparticles (NPs). The main objective was to investigate, using Box–Behnken design, the factors affecting particle size of PLGA NPs encapsulating BSA. Methods PLGA nanoparticles containing BSA were prepared by double emulsion solvent evaporation (DESE) method. Concentrations of PLGA, BSA and polyvinyl alcohol (PVA) as well as volume ratio (VR) of the primary emulsion to external aqueous phase in DESE were hypothesized to be the key four independent parameters affecting particle size. Results The particle sizes obtained from 27 experiments were in the range of 266 nm to 656 nm. The model showed that as a general rule, PVA, VR and PLGA had a direct significant effect and on the particle size, while the effect of BSA was negligible. Conclusion The independent factors appear to be affecting the size through their effects on viscosity which could be regarded as the most important factor. Keywords double emulsion, PLGA, BSA, volume ratio, poly vinyl alcohol, Box–Behnken design